Whey Protein Delays Gastric Emptying and Suppresses Plasma Fatty Acids and Their Metabolites Compared to Casein, Gluten, and Fish Protein - Stanstrup, Jan; Schou, Simon S; Holmer-Jensen, Jens; Hermansen, Kjeld; Dragsted, Lars O (Journal of proteome research, 2014)
Whey protein has been demonstrated to improve fasting lipid and insulin response in overweight and obese individuals. To establish new hypotheses for this effect and to investigate the impact of stomach emptying, we compared plasma profiles after intake of whey isolate (WI), casein, gluten (GLU), and cod (COD). Obese, nondiabetic subjects were included in the randomized, blinded, crossover meal study. Subjects ingested a high fat meal containing one of the four protein sources. Plasma samples were collected at five time points and metabolites analyzed using LC-Q-TOF-MS. In contrast to previous studies, the WI meal caused a decreased rate of gastric emptying compared to the other test meals. The WI meal also caused elevated levels of a number of amino acids, possibly stimulating insulin release leading to reduced plasma glucose. The WI meal also caused decreased levels of a number of fatty acids, while the GLU meal caused elevated levels of a number of unidentified hydroxy fatty acids and dicarboxylic fatty acids. Also reported are a number of markers of fish intake unique to the COD meal.